Screen time in children and adolescents during the COVID-19 pandemic - Bojana Vuković; Sanja Živanović; Bojana Mastilo; Ivana Zečević (Биомедицинска истраживања, 2023)
Introduction: With the beginning of the pandemic caused by the COVID-19 virus, restrictions on movement, the so-called "lockdown" were applied by many governments. As a result of these actions taken against the transmission of the COVID-19 virus, the use of digital devices has increased, i.e. the time spent in front of screens has increased. Methods: This paper dealt with a bibliometric analysis of scientific publications on the topic of screen time in children and adolescents during the COVID-19 pandemic. The Dimensions database was chosen as the data source. No time frame is given, but given the topic, publications from 2020-2023 are included in the analysis. The data were analyzed in the VOSviewer program, specified for bibliometric and visual data analysis. Results: Map of word co-occurrence show that there are three different clusters. In the red cluster, consisting of 53 terms, the most frequent terms are sleep (124), lifestyle (103) and restriction (83), while in the green cluster, consisting of 41 terms, family (126), education (88), relationship (86) are the most represented. The blue cluster consists of significantly fewer terms, 12 of them, of which anxiety (91), symptom (81), depression (58) are the most represented. Conclusion: Based on the bibliometric analysis, we can conclude that the scientists were mostly concerned with the impact of the screen time phenomenon on the physical health of children and adolescents. In addition, screen time has been linked to mental health, education and socio-emotional relationships.
Keywords: COVID-19; screen time; children; adolescents